Effect of support supervision on maternal and newborn health services and practices in Rural Eastern Uganda - Kisakye, Angela N.; Muhumuza Kananura, Rornald; Ekirapa-Kiracho, Elizabeth; Bua, John; Akulume, Martha; Namazzi, Gertrude; Namusoke Kiwanuka, Suzanne (Global Health Action, 2017)
Support supervision is one of the strategies used to check the quality of services provided at health facilities. From 2013 to 2015, Makerere University School of Public Health strengthened support supervision in the district of Kibuku, Kamuli and Pallisa in Eastern Uganda to improve the quality of maternal and newborn services. Objective: This article assesses quality improvements in maternal and newborn care services and practices during this period. Methods: District management teams were trained for two days on how to conduct the supportive supervision. Teams were then allocated particular facilities, which they consistently visited every quarter. During each visit, teams scored the performance of each facility based on checklists; feedback and corrective actions were implemented. Support supervision focused on maternal health services, newborn care services, human resources, laboratory services, availability of Information, education and communication materials and infrastructure. Support supervision reports and checklists from a total of 28 health facilities, each with at least three support supervision visits, were analyzed for this study and 20 key-informant interviews conducted. Results: There was noticeable improvement in maternal and newborn services. For instance, across the first, second and third quarters, availability of parenteral oxytocin increased from 57% to 75% and then to 82%. Removal of retained products increased from 14% to 50% to 54%, respectively. There was perceived improvement in the use of standards and guidelines for emergency obstetric care and quality of care provided. Qualitatively, three themes were identified that promote the success of supportive supervision: changes in the support supervision style, changes in the adherence to clinical standards and guidelines, and multi-stakeholder engagement. Conclusion: Support supervision helped district health managers to identify and address maternal and newborn service-delivery gaps. However, issues beyond the jurisdiction of district health managers and facility managers may require additional interventions beyond supportive supervision.
Keywords: Support supervision; Implementation science; Human resource; Health workers; Maternal and newborn services